Hubungan antara Self Efficacy dengan Flow Academic terhadap Mata Pelajaran Matematika Siswa Kelas XII SMA Adabiah 2 Kota Padang - Ramadan, Rezky (YASIN, 2024)
This study aims to explore the relationship between self efficacy and academic flow in mathematics subjects among grade XII students of SMA Adabiah 2 Padang. The independent variable in this study is self efficacy, while the dependent variable is academic flow. The sampling technique used was simple random sampling, with a sample size of 135 grade XII students of SMA Adabiah 2 Padang. To test the validity and reliability, the Alpha Cronbach technique was used, with a self efficacy scale consisting of 15 items and a coefficient of 0.760, and an academic flow scale consisting of 17 items with a coefficient of 0.877. Data analysis was carried out using the parametric method using the Pearson product moment correlation technique, with the help of SPSS 27.0 software. The results of the analysis show a correlation coefficient of r = 0.536 and a p value of 0.000, which means the alternative hypothesis (H1) is accepted and the null hypothesis (H0) is rejected. The findings of this study indicate a positive relationship between self-efficacy and academic flow in mathematics subjects in grade XII students of SMA Adabiah 2 Padang.